2015
DOI: 10.1021/acs.biochem.5b00495
|View full text |Cite
|
Sign up to set email alerts
|

Role of GxxxG Motifs in Transmembrane Domain Interactions

Abstract: Transmembrane (TM) helices of integral membrane proteins can facilitate strong and specific noncovalent protein-protein interactions. Mutagenesis and structural analyses have revealed numerous examples in which the interaction between TM helices of single-pass membrane proteins is dependent on a GxxxG or (small)xxx(small) motif. It is therefore tempting to use the presence of these simple motifs as an indicator of TM helix interactions. In this Current Topic review, we point out that these motifs are quite com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
158
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(163 citation statements)
references
References 164 publications
3
158
0
2
Order By: Relevance
“…Previous studies showed that mutations and truncations in the TMD indeed affect membrane fusion and viral infectivity (8-11). Presence of a GxxxG motif, often implicated in oligomeric assembly of TM helices (12), suggests clustering of TMDs in membrane (Fig. S1).…”
mentioning
confidence: 99%
“…Previous studies showed that mutations and truncations in the TMD indeed affect membrane fusion and viral infectivity (8-11). Presence of a GxxxG motif, often implicated in oligomeric assembly of TM helices (12), suggests clustering of TMDs in membrane (Fig. S1).…”
mentioning
confidence: 99%
“…The impact of small residues on transmembrane helix-helix interactions is likely not only of a passive nature, but also involves active forces, such as van der Waals interactions and C α H⋯O=C hydrogen bonds. [5,6] The energetic stability of small-residue packing markedly depends on the protein sequence and membrane lipids, [6] although the regulation rules are poorly understood.…”
mentioning
confidence: 99%
“…The assembly of such complexes frequently depends on interactions between TMDs, a topic which has received considerable attention over the past two decades. TMD-TMD interactions involve all kinds of physical forces known to stabilize proteins and their interactions; these include van der Waals forces, hydrogen bonds and aromatic interactions2345. In addition, charge-charge interactions have previously been implied in TMD-TMD interactions6.…”
mentioning
confidence: 99%